Public Space, Technology, and Humanity in Inclusion Education Policy Dynamics in Indonesia - Miftah, Muhammad; Choir, Abu (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
Discrimination in the education world is not only incidental under certain conditions. The injustice sometimes